2017
DOI: 10.1186/s13071-017-2079-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Taenia saginata (Cestoda: Cyclophyllidea) from Lao People’s Democratic Republic and northeastern Thailand based on mitochondrial DNA

Abstract: Background Taenia saginata is a tapeworm found in cattle worldwide. Analysis of genetic diversity in different geographical populations of T. saginata not only helps to understand the origin, transmission and spread of this organism, but also to evaluate the selection pressures acting on T. saginata and how it is responding to them. However, there are few reports of the genetic variability of T. saginata populations in different regions of the world, including Lao PDR and Thailand. We report the genetic divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Differently from the other studies in the central, north and northeastern areas of Lao PDR, where cases of T . asiatica were not found [ 12 , 14 , 15 ], in the east part of Savannakhet province ( Fig 1 ) we could detect the presence of 3 species of human Taenia species in Sepon district that border Vietnam. The prevalence of Taenia eggs in KK was not high as presented by Okello et al [ 14 ] which detected percentages as high as 46%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Differently from the other studies in the central, north and northeastern areas of Lao PDR, where cases of T . asiatica were not found [ 12 , 14 , 15 ], in the east part of Savannakhet province ( Fig 1 ) we could detect the presence of 3 species of human Taenia species in Sepon district that border Vietnam. The prevalence of Taenia eggs in KK was not high as presented by Okello et al [ 14 ] which detected percentages as high as 46%.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, in a recent study, 15 haplotypes of T . saginata were obtained from 30 isolates from Khammouane Province, central Lao PDR [ 15 ]. An extensive study on the prevalence of taeniasis in Lao PDR with whole country coverage reported the presence of mainly T .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, several phylogenetic analyses were performed and all demosntrated genetic diversity in F. hepatica [4] , L. tropica [5] , T. saginata [6] , E. multilocularis [7] , G. lamblia [8] ; Blastocystis spp. [9] ; E. granulosus [10] .…”
Section: Applicationsmentioning
confidence: 99%
“…Taenia saginata, Taenia solium, and Taenia asiatica are responsible for human taeniasis. Among them, T. saginata and T. solium are distributed globally, while T. asiatica is mostly distributed in Asian countries [1][2][3][4][5]. The symptomatology of infection is broad, but the most frequent and distinctive symptoms are the discharge of proglottids, abdominal pain, weight loss, nausea, and fever [6].…”
Section: Introductionmentioning
confidence: 99%